The narrative segment in the novel The violence of time, by Miguel Gutiérrez - Malpartida Robles, Juan Miguel (2022)
This article deals with the narrative segment in Miguel Gutiérrez novel, The violence of time, about how it organizes narrative discourse; how, through it, meaning and meaning flow freely in the succession of the chapters, each organized in two parts. It is a structuralist vision that validates the organization of the discourse: the story that the story tells in the novel. We do not pay attention to the structure, but to the evolution of the story, narrative segment after narrative segment. We call this content unit thus, narrative segment, to emphasize that it is an entity of measurable nature, as an expression of content, despite being only substance, not form.